Women’s experiences of the Odon Device to assist vaginal birth and participation in intrapartum research: a qualitative study in a maternity unit in the Southwest of England - Natalie S Blencowe; Emily J Hotton; Erik Lenguerrand; Julia Wade; Joanna F Crofts; Tim J Draycott (BMJ Open)
Objective To investigate women’s experiences of having a birth assisted by the Odon Device (an innovative device for assisted vaginal birth) and participation in intrapartum research.Design Qualitative semistructured interviews and observations undertaken in the context of case study work embedded in the ASSIST feasibility study.Setting A tertiary referral National Health Service (NHS) maternity unit in the Southwest of England, between 8 October 2018 and 26 January 2019.Participants Eight women, four operators and 11 midwives participated with eight observations of the assisted vaginal birth, eight interviews with women in the postnatal period, 39 interviews/reflections with operators and 19 interviews with midwives. Women in the case study research were recruited from participants in the main ASSIST Study.Intervention The Odon Device, an innovative device for assisted vaginal birth.Results Thirty-nine case studies were undertaken. Triangulation of data sources (participant observation, interviews with women, operators and midwives) enabled the exploration of women’s experiences of the Odon Device and recruitment in the intrapartum trial. Experiences were overwhelmingly positive. Women were motivated to take part by a wish for a kinder birth, and because they perceived both the recruitment and research processes (including observation) to be highly acceptable, regardless of whether the Odon-assisted birth was successful or not.Conclusions Interviews and observations from multiple stakeholders enabled insight into women’s experiences of an innovative device for assisted vaginal birth. Applying these qualitative methods more broadly may illuminate perspectives of key stakeholders in future intrapartum intervention research and beyond.Trial registration number ISRCTN10203171; ASSIST Study registration; https://doi.org/10.1186/ISRCTN10203171.